Studi Keputusan Pembelian Makanan Oleh-Oleh Khas Surabaya: Peran Brand Awareness dan Kualitas Produk - Wisesa, Candra Purba (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2021)
Travelling is a fun and memorable activity. During tourism activities, tourists not only walk around but also go shopping. Including one of them is to buy souvenirs typical of the tourist areas visited. This study aims to analyze the effect of brand awareness and product quality on purchasing decisions. Respondents in this study were consumers who were at least 20 years old who had made a purchase. The sampling method uses non-probability sampling, and the sampling technique using judgmental sampling. The sample used in this study amounted to 220. The data is collected using a questionnaire and analyzed using multiple linear regression. The result shows that brand awareness influences purchasing decisions. Product quality affects purchasing decisions.